The Effect of 'Fish Diversity' Book in Kampar District on the Learning Motivation and Obstacles of Kampar High School Students through Online Learning during the COVID-19 Period - Yustina Yustina; Lilia Halim; Imam Mahadi (Journal of Innovation in Educational and Cultural Research, 2020)
The study aims to analyze the effect of the fish diversity book in Kampar District on the learning motivation and obstacles of Kampar High School students through online learning during the COVID-19 period. This type of research is a quasi-experimental study with research subjects in class XI SMA Kampar (Kampar High School). In its implementation, students were given a motivational questionnaire in the beginning, after that they were given the task of studying the types of fish in Kampar through the book files of fish diversity in Kampar District through online learning. After online learning, the post-test was given using a questionnaire evaluation of the motivation and online learning obstacles questionnaire. Parameters: learning motivation with five indicators, ten indicators of online obstacles. Motivation data collection using pre-test and post-test. Data is presented and analyzed descriptively. The results obtained an average score of post-test student learning motivation (77.7) increased compared to before studying diversity book (65.9) with an N-gain index of 0.34, 74% of respondents said online learning was more effective, 50% of respondents stated the ordinary school is better than online learning. The implementation of fish species diversity books through online learning is effective in increasing student learning motivation, but it is less effective in motivating desires, appreciation, and not being attractive enough. The obstacles of online learning at Kampar High School include internet network facilities and field practicum during the COVID-19 period.